International Financial Integration - Lane, Philip (IMF Working Papers; Working Paper ;, 2003)
In recent decades, the foreign assets and liabilities of advanced economies have grown rapidly relative to GDP, with the increase in gross cross-holdings far exceeding changes in the size of net positions. Moreover, the portfolio equity and FDI categories have grown in importance relative to international debt stocks. This paper describes the broad trends in international financial integration for a sample of industrial countries and seeks to explain the cross-country and time-series variation in the size of international balance sheets. It also examines the behavior of the rates of return on foreign assets and liabilities, relating them to "market" returns.